The Influence of Hotel Tax and Restaurant Tax Receipt on Regional Tax Revenue - Yulisa Indah Mawarni; Lili Indrawati (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
This study aims to examine the influence of hotel tax revenue and restaurant tax on Garut Regency regional tax revenue in 2017-2021. This research was conducted using a quantitative descriptive approach. The research was conducted at the Regional Financial and Asset Management Agency (BPKAD) Garut Regency. The type of data used is documentary data sourced from secondary data in the form of time series data. The data analysis tool used is multiple regression. The results showed that the hotel tax had no influence on the Garut Regency local tax, the restaurant tax had a partially positive significant influence on the Garut Regency regional tax. Simultaneously shows that hotel taxes and restaurant taxes simultaneously have a positive influence on Garut Regency local taxes.